2021
DOI: 10.21037/jtd-20-3564
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of primary graft dysfunction is higher according to the new ISHLT 2016 guidelines and correlates with clinical and molecular risk factors

Abstract: Background: Primary graft dysfunction (PGD) is the most important determinant of morbidity and mortality after lung transplantation, but its definition has evolved over the past decade. The implications of this refinement in clinical definition have not been evaluated. In this single-center study, we compared PGD incidence, risk factors, and outcomes using the 2005 and the updated-2016 International Society of Heart and Lung Transplantation guidelines for PGD grading in lung transplant patients. Methods: In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…We found a correlation between sRAGE levels and the severity of PGD in one of 12 pairwise comparisons. Pretransplant samples showed lower levels of sRAGE in patients with greater PGD severity, which is consistent with findings reported by Daoud et al 5 . sRAGE levels were increased in postoperative samples at T24–72 h in our study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found a correlation between sRAGE levels and the severity of PGD in one of 12 pairwise comparisons. Pretransplant samples showed lower levels of sRAGE in patients with greater PGD severity, which is consistent with findings reported by Daoud et al 5 . sRAGE levels were increased in postoperative samples at T24–72 h in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the rates of PGD in this series were higher than those reported in large multicenter studies 24 , but the risk factors and outcomes associated with PGD were similar. The higher rates in our study may be due to the use of the updated 2016 ISHLT scoring guidelines, which increase detection of PGD, particularly in extubated patients 5 . However, our PGD rates were not entirely different from those in a recent international multicenter www.nature.com/scientificreports/ cohort 25 .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A recent study by our group showed that the updated guidelines could increase detection of PGD by 42%. 22 In addition, intraoperative ECMO was not included in the LTOG analysis, and there could certainly be differences among patient populations. Substantial differences in PGD outcomes across studies are not uncommon and can be explained by differences in guidelines, the timing of blood gas collections, availability of oxygen saturation and blood gas data in extubated patients, differences in interpretation of chest radiograph results, and differences in ventilator-related parameters.…”
Section: Discussionmentioning
confidence: 99%